Antioxidant and cytoprotective properties of loganic acid isolated from seeds of Strychnos potatorum L. against heavy metal induced toxicity in PBMC model. (2nd January 2022) - Abirami, Alagarsamy; Sinsinwar, Simran; Rajalakshmi, Perumal; Brindha, Pemaiah; Rajesh, Yamajala B. R. D.; Vadivel, Vellingiri
Abstract: Present work carried out with the objectives to isolate active component of S. potatorum and also to evaluate its free radical scavenging activity and preventing capacity against heavy metal toxicity. Solvents of different polarity were used to prepare crude extracts of S. potatorum seeds and screened for antioxidant activity. Among the crude extracts, methanolic extract was found to exhibit higher antioxidant activity (81.22%) which was fractionated by liquid-liquid partitioning method. Among the different fractions (LF1-LF4), LF-2 showed higher antioxidant activity (98.24%) as compared to other three liquid fractions and hence LF-2 was further purified by column chromatography. Among nine column fractions (CF1-CF9), fraction CF-7 was found to have higher antioxidant activity (92.14%), which was further analyzed using LC-MS and NMR and identified as loganic acid. In vitro radical scavenging assays showed remarkable antioxidant activity of loganic acid in terms of DPPH scavenging (IC50 149 µg/ml), superoxide radical scavenging (IC50 632.43 µg/ml) and hydroxyl radical scavenging (IC50 29.78 µg/ml). Loganic acid exhibited 81% prevention of heavy metal toxicity through the mechanism of inhibiting ROS generation (2046 AU vs. 5264 AU in control) and lipid peroxidation (95.01%). Thus, the active compound (loganic acid) isolated from S. potatorum has strong free radical scavenging activity and remarkable cyto-protective effect against heavy metal mediated toxicity.